The Influence of ROA, ROE, NPM, and GPM on Stock Returns of Technology Companies Listed on the Indonesian Stock Exchange - Riani, Ayundah; Mala, Chajar Matari Fath (Eastasouth Institute, 2024)
This research examines the influence of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Gross Profit Margin (GPM) on the stock returns of technology businesses listed on the Indonesia Stock Exchange. This analysis comprises all legally registered technological businesses listed on the Indonesian Stock Exchange from 2019 to 2022. Currently, the website idx.co.id displays about 43 technological businesses that have been officially registered. This study focuses on ROA) and NPM as crucial metrics for predicting stock returns in the technology industry. It specifically highlights the possibly negative impact of ROE. The minimal impact of GPM implies that investors may place more emphasis on evaluating possible stock returns in the technology sector using other metrics. It is advisable to do more analysis on the factors that influence returns in order to have a thorough comprehension.